Content of amino acids and biogenic amines in stored meat as a result of a broiler diet supplemented with β-alanine and garlic extract - Wojciech Wójcik; Olga Świder; Monika Łukasiewicz-Mierzejewska; Krzysztof Damaziak; Julia Riedel; Agata Marzec; Michał Wójcicki; Marek Roszko; Jan Niemiec (Poultry Science, 2024)
ABSTRACT: Poultry meat is a highly esteemed product among consumers. However, the emphasis on increasing body weight has led to a rise in the proportion of rapidly shrinking fibers, adversely affecting the quality and shelf life of poultry meat. With a growing awareness of dietetics among consumers, there is an increasing challenge to produce chicken meat that is not only free of antibiotics but also beneficial for dietary and health reasons. Biogenic amines (BA) can serve as indicators of meat freshness and quality. While they play vital roles in the body, excessive consumption of BA can have toxic and carcinogenic effects. The objective of this study was to examine the impact of supplementing feed with garlic extract and β-alanine (β-Ala) on the formation of BA and amino acid (AA) levels in the breast and leg muscles of chickens stored under aerobic chilling conditions. The muscles were obtained from chickens fed with garlic extract and β-Ala in quantities of 0.5 and 2% for each additive, as well as 0.5 and 2% of their combination. Analyses were conducted on d 1, 3, 5, 7, and 10 of storage. β-Ala supplementation increased the proportion of this AA in breast (P < 0.01) and leg muscles (P < 0.01), along with a rise in the proportion of nonessential AA (NEAA; sum of aspartic, aspartic acid, glutamic, glutamic acid, serine, β-Ala, and proline) (P < 0.01). The levels of BA changed during storage in breast and leg muscles (P < 0.001). The applied diet significantly influenced the formation of putrescine (P = 0.030), phenylethylamine (P = 0.003), agmatine (P = 0.025), and total BA (P < 0.001) in breast muscles. On the 10 d of storage, the breast muscles exhibited the lowest BA index (BAI) in the group, with a diet supplemented with 0.5% garlic extract and 0.5% β-Ala (P < 0.05). The leg muscles showed a similar BA trend as the breast muscles. These supplements may be utilized in production to augment the protein content of chicken muscles and potentially decrease the BAI index during meat storage.